Elementary proof of strong normalization for Atomic F - Ferreira, Fernando (2016)
We give an elementary proof (in the sense that it is formalizable in Peano arithmetic) of the strong normalization of the atomic polymorphic calculus Fat (a predicative restriction of Girard’s system F).